Place et rôle de la figure féminine chez Emile Zola à travers l’étude de trois oeuvres: L’assommoir, Germinal et La Bête Humaine - Payet, Marie (Verbum – Analecta Neolatina, 2002)
The main theme in Émile Zola’s literary work is to reconsider man’s place in the universe, his future and furthermore, the place and the role of works of art in society. Zola, first of all places his characters into an environment which determines them and limits their freedom. The material proposed here is an extract of a research on the character system established by Émile Zola while creating his social fresco, Les Rougon-Macquart.